2018
DOI: 10.1016/j.prp.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transcription factor SOX2 in synovial sarcoma and other soft tissue tumors

Abstract: The data confirms previous studies reporting SOX2 and H3K27me3 expression in synovial sarcoma and reveals that both biomarkers are related to each other. It strengthens the notion that the tumor type is driven by epigenetic processes similar to those that are operating in pluripotent stem cells. The relevance of these parameters in the pathway pathology of synovial sarcoma, i.e. the timing and dosing of SOX2 and H3K27me3 expression initiated by the SS18-SSX driver mutation together with the interplay of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 161 publications
(136 reference statements)
1
10
0
Order By: Relevance
“…We found that SOX2 is expressed in 28% of an array of 88 sarcoma patients, being UPS, synovial sarcomas and Ewing sarcomas those presenting a higher percentage of positive cases in concordance with the results of previous reports [43,44]. In our series, SOX2 expression significantly correlated with tumor grade, poor differentiation, invasive potential and poor patient survival.…”
Section: Discussionsupporting
confidence: 91%
“…We found that SOX2 is expressed in 28% of an array of 88 sarcoma patients, being UPS, synovial sarcomas and Ewing sarcomas those presenting a higher percentage of positive cases in concordance with the results of previous reports [43,44]. In our series, SOX2 expression significantly correlated with tumor grade, poor differentiation, invasive potential and poor patient survival.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, ATP-dependent chromatin remodelers, such as SWI/SNF, ISWI, and CHD, are implicated in tumor initiation, sarcomagenesis and maintenance of a stem-like phenotype in STS [17], namely in myxoid liposarcoma [74], SS [75], or RMS [76]. Table 1 summarizes the CSC markers that have been used to identify, isolate and characterize CSCs in different STS subtypes.…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…Myxoid Liposarcoma SWI/ SNF, ISWI and CHD [74] In vitro MPNST 1 Nestin [36] In vitro and in vivo Rhabdomyosarcoma ALDH [39] In vitro and in vivo CD133 [19][20][21] In vitro, in vivo and patient samples DNMT3B [68] In vitro EZH2 [69] In vitro and in vivo Nestin [19,27,[33][34][35] In vitro, in vivo and patient samples NOTCH-YAP1-Sox2 [62] In vitro, in vivo and patient samples Side Population [54] In vitro, in vivo and patient samples Embryonic stem cell transcription factors [64] In vitro, in vivo and patient samples SWI/ SNF, ISWI and CHD [76] In vitro, in vivo and patient samples Synovial Sarcoma ALDH [40] In vitro Active Wnt pathway [77] In vitro and in vivo BMI1 [23] In vitro CD133 [23,25] In vitro and patient samples CXCR4 [28] In vitro, in vivo and patient samples EZH2 [70][71][72] In vitro, in vivo and patient samples SWI/ SNF, ISWI and CHD [75] Patient samples UPS 2 Side Population [54] In vitro, in vivo and patient samples ABC transporters [51] In vitro CD133 [51] In vitro Embryonic stem cell transcription factors [51] In vitro 1 MPNST: Malignant peripheral nerve sheath tumor; 2 UPS: Undifferentiated pleomorphic sarcoma.…”
Section: Sts Subtype Csc Marker/feature Evidencementioning
confidence: 99%
“…In addition to their essential functions during embryonic development, these genes could exert diverse functions in cancer. In certain human tumors, they might represent valuable tools to predict recurrence and tumor plasticity, although such prognostic value is far from being established [ 79 , 89 , 90 , 91 , 92 , 93 , 94 ].…”
Section: Mechanisms Of Hypoxia-induced Cancer Stem Cellsmentioning
confidence: 99%